Study on awareness of social security for taxi driver in Melaka Tengah / Norliza Abd Basir - Abd Basir, Norliza (Faculty of Administrative Science and Policy Studies, 2013)
Social Security Organization (SOCSO) is a body set up to manage, enforce and implement the Employees' Social Security Act. This organization provides social security protection by social insurance. It is include cash and medical benefit, provision of artificial aids and rehabilitation to employees to reduce the distressed and to offer financial guarantees and protection to the family. No provision in the SOCSO scheme to cover self-employed in Malaysia. Base on this new issue that the Social Security Organization introduce the protection for taxi driver starting 2015, this study on awareness of selfemployed for taxi driver is made. Beside that this study show the result on the necessity for self-employed which is taxi driver to contribute in social security. In this study Taxi Driver in Melaka Tengah is selected as respondents in order to get result for this issue.